Switched Quasi-Logarithmic Quantizer with Golomb–Rice Coding - Vucic, Nikola; Peric, Zoran; Dincic, Milan (Elektronika ir Elektrotechnika, 2017)
This paper proposes a model of switched quasi-logarithmic quantizer for speech signal based on G.711 standard with usage of Golomb-Rice (GR) coding. In order to achieve better performances a method with switched quantizer is applied. Variance range is split into quantizers and for each of them a separate quantizer is designed, i.e. the support region is determined. Optimization of the support region and choice of the parameter μ is done in order to obtain a quantizer that obeys G.712 standard and gives minimal average bit rate. Every quantizer within the variance range has own model with a two-stage coder. Two stages are introduced with purpose to reduce the bit rate, whereby GR code plays its role as Variable Length Code (VLC). The first stage uses a GR coder for coding segments of the quantizer’s support region, whereas the second stage applies the coding method with fixed code lengths for coding cells within a segment. GR has simpler and cheaper hardware realization than other VLC codes, Huffman’s for instance, with very satisfying results regarding quality of quantized signal.DOI: http://dx.doi.org/10.5755/j01.eie.23.4.18727